Potential Role of Lactoferrin and Heparin in COVID-19: A Review - Hoxha, Bianka; Hodaj, Arvjola (European Scientific Journal, ESJ, 2021)
Aim: The aim of the research is to evidence the potential role of lactoferrin (LF) and heparin in coronavirus disease 2019 (COVID-19). Moreover, we discuss and underline the mechanisms involved in this possible association. Methods: PubMed and Scopus databases were used to conduct the literature search. Findings and Conclusion: Studies have widely proven the principal activity of LF, in the inflammatory process, as an anti-inflammatory and immunomodulatory glycoprotein. Evidence shows that LF has important antibacterial and antiviral effects against human and animal pathogens. Heparin and LF could reduce viral entry by preventing the attachment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as a result of competitive binding to heparan sulfate proteoglycans (HSPGs). Clinical studies are necessary to specify LF and heparin mechanisms of action and the therapeutical dose in patient affected with COVID-19.